Groundwater level effects on greenhouse gas emissions from undisturbed peat cores - Erne Blondeau; Gerard L. Velthof; Marius Heinen; Rob F.A. Hendriks; Anneke Stam; Jan J.H. van den Akker; Monne Weghorst; Jan Willem van Groenigen (Geoderma)
Peat soils store a large part of the global soil carbon stock, which can potentially be lost when they are drained and taken into cultivation, resulting in CO2 emission and land subsidence. Groundwater level (GWL) management has been proposed to mitigate peat oxidation, but may lead to increased emissions of nitrous oxide (N2O) and methane (CH4).The aim of this experiment was to study trade-offs between greenhouse gas emissions from peat soils as a function of GWL. We incubated 1 m deep, 24 cm diameter undisturbed bare soil cores, after removal of the grass layer, from three contrasting Dutch grassland peat sites for 370 days at 16 °C. The cores were subjected to drying-wetting cycles, with the GWL varying between near the soil surface to 160 cm below the surface. We measured gas fluxes of CO2, N2O and CH4 from the soil surface, extracted pore water for DOC and mineral nitrogen analysis, and measured soil hydraulic and shrinkage characteristics.Emissions of CO2 increased after lowering the GWL, but showed different GWL-response curves during rewetting of the soil. On average, highest CO2 emissions of 1.5 g C·m−2 day−1 were found at a GWL of 80 cm below the surface. However, the 0 cm GWL was the only treatment with significantly lower CO2 emissions than other GWLs. Cumulative CO2 emissions differed significantly between sampling sites. Emissions of N2O showed a different response, peaking at GWL heights above −20 cm, particularly after a recent GWL rise. Though not significantly different, the highest N2O emissions were measured at the 0 cm GWL treatment. We confirmed this pattern for N2O in un-replicated soil cores with grass sward, although emission values were lower in these cores due to the root uptake of mineral nitrogen. CH4 emissions or −uptake remained low under any GWL. We conclude that raising the GWL is a successful strategy to reduce CO2 emissions from peat oxidation. However, raising the GWL close to the soil surface could lead to N2O emissions that negate any gains in terms of global warming potential. Our results suggest that raising the GWL in peat grasslands to −20 cm creates such a risk. A constant GWL at the surface (0 cm) would be preferential for mitigating both CO2 and N2O emissions, although such conditions don’t allow for agricultural grass production (mowing or grazing).